Evaluasi Kebijakan Pengembangan Kawasan Minapolitan di Kabupaten Bogor - Eko Budi Santoso; Reydonnyzar Moenek; Mohamad Nurpahdi (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
Abstract Minapolitan development is mostly carried out in Indonesia, including by the Bogor Regency. The development of the Minapolitan area in Bogor Regency has been carried out since 2010, which is based on the Bogor Regency Decree Number 523.31/227/Kpts/Huk/2010 concerning the Establishment of Minapolitan Areas in Bogor Regency, which stipulates the Minapolitan area in Bogor Regency covering 4 sub-districts namely Ciseeng District, Parung, Gunungsindur and Kemang based on aquaculture. The development of minapolitan in Bogor Regency also indicates the existence of problems that need to be resolved. This study seeks to evaluate the development policy of Minapolitan in Bogor Regency. The method used was descriptive qualitative research. The policy evaluation theory used is based on William Dunn's thought for policy evaluation covering 6 dimensions: effectiveness, efficiency, adequacy, distribution, responsiveness, and accuracy. Collection of data through interviews, direct observation, and documentation. The results of the study show that from these 6 dimensions 2 dimensions show good conditions that support the success of policies, namely dimensions of effectiveness and efficiency. While there are 4 dimensions that have weaknesses, namely responsiveness, distribution, adequacy and accuracy of policies. Suggested several things: 1) need to increase monitoring on the provision of the main transportation infrastructure for regional connectivity in wider region; 2) increasing community power through empowerment; 3) increasing the local government facilitation togethe with community efforts in increasing the awareness of millennial generations on the prospects for developing the primary sector in the region; and 4) Need to increase fairness in the distribution of government assistance, as well as facilitation of local governments in maintaining the stability of fish feed prices. Keywords: policy evaluation, minapolitan, zone development, Bogor Regency